KONSEP MERDEKA SEBAGAI LANDASAN PENDIDIKAN DI ERA KURIKULUM MERDEKA BELAJAR - Lora Devian; Neviyarni; Irda Murni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Educational philosophy determines educational decisions, alternatives and choices that are guided by education and curriculum developers. The emergence of the term "Freedom to learn" is a new policy program of the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) launched by the Indonesian Minister of Education and Culture of the Advanced Indonesia Cabinet, Nadiem Anwar Makarim. This independent learning curriculum aims to answer the challenges of education in the era of the industrial revolution 4.0. The method used in this research is literature research (library research). The results of the literature review in this study concluded that the concept of independent learning curriculum education integrates literacy skills, knowledge skills, skills and attitudes as well as mastery of technology. The independent learning policy is based on four philosophical views, namely progressivism, constructivism, humanism, and anthropological philosophy. In addition, the philosophical basis for the policy of independent learning can also be found in Ki Hadjar Dewantara's view of education.